Integration of Information and Communication Technologies in Police Training: An Analysis of Advantages and Challenges - Avila Niño, Fredy Yesid (2025)
This article analyzes the advantages, challenges, and didactic opportunities of using ICT in police education at the Rafael Reyes Police School in Santa Rosa de Viterbo, Boyacá, Colombia, where the Technical Professional in Police Service is offered, highlighting the importance of a solid foundation to meet the demands of the service. Upon completion of the training process and approval of the program, students enter the Colombian National Police as Patrol Officers. A qualitative methodology was used, with structured surveys applied to uniformed police instructors, civilian hourly instructors, and police students. The analysis focuses on the teaching staff, while the results from the students will be addressed in a future publication. The research reveals an increasing acceptance of ICT in police training, with a growing interest in their integration into the classroom. The benefits of these technologies include providing up-to-date information, promoting interactive learning, and preparing students for real-life situations. However, the need for intuitive technological solutions for successful adoption is emphasized. Continuous teacher training in the use of ICT is essential, as well as the creation of interactive and multimedia educational content to foster student participation. Implementing feedback and continuous evaluation mechanisms allows measuring the impact of ICT on learning and making necessary adjustments. Personalizing the integration of ICT to meet the specific needs of police training and fostering ongoing research through collaboration between educational institutions, police forces, and technology experts are key recommendations for advancing in this field.